Assessing the impact of management by objectives on non-financial dimensions of organizational performance - Chinelo Patience Ohanyere; Ekwutosi Theresa Ezeanorue; Emeka Alex Akwaeze (RTTM, 2026)
This study examined the impact of Management by Objectives (MBO) on the non-financial dimensions of organizational performance in a commercial bank in Awka South LGA, Anambra State, Nigeria. The research adopted a descriptive survey design, targeting 50 employees across top, middle, and junior management levels. Data were collected using structured questionnaires and analyzed through descriptive statistics, including mean and standard deviation, as well as Pearson correlation to test the relationship between MBO and non-financial performance indicators. The study achieved a 95% questionnaire return rate, with 100 out of 105 questionnaires returned, indicating adequate data for analysis. Respondents comprised 62% males and 38% females, with the majority aged 31–40 years (47%). Most respondents were married (58%) and predominantly held junior management positions (52%). Analysis of Management by Objectives (MBO) revealed positive impacts on non-financial performance, including boosting employee motivation (3.72), optimizing resources (3.95), setting customer-centric objectives (2.80), ensuring high-quality service delivery (3.88), and promoting innovation (3.84), with a grand mean of 3.64. Pearson correlation analysis showed a strong positive relationship between MBO and non-financial performance (r = 0.667, p = 0.62671), indicating that effective MBO implementation enhances operational outcomes beyond financial metrics. The study concludes that adopting MBO practices contributes significantly to holistic organizational performance by improving workforce productivity, service delivery, and innovation. Recommendations include continuous training on MBO practices, periodic review of objectives, and active employee participation to sustain improved non-financial outcomes